THE EFFECTS OF PULMONARY REHABILITATION IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Özlem Levent; Yeşim Kurtaiş Gürsel (Archives of Rheumatology, 2003)
The purpose of this study was to compare the effects of pulmonary rehabilitation (PR) on physiologic and psychosocial outcomes in patients with chronic obstructive pulmonary disease (COPD) with thase of education alone. Twentythree patients with COPD were randomly assigned to either a 3 days per week for 8 weeks comprehensive pulmonary rehabilitation program (exercise group) or to 8 weeks education program (control group ). Compared with education alone, pulmonary rehabilitation produced a greater improvement in exercise endurance, 6-minute walking test, exertional dyspnea and depression. Measures of lung function and arterial blood gases did not differ between groups, whereas diffusion capacity significantly improved in the exercise group. There was a significant improvement in the quality of life in both groups. These findings suggest that 8-week pulmonary rehabilitation program may be beneficial for COPD patients. Improvement in functional exercise capacity, even without an increase in maximal exercise capacity, are helpful for reducing dyspnea and depression, improving quality of life parameters in patients with COPD.